Predictores de fracaso del manejo conservador en pacientes con obstrucción intestinal - Luján Rodríguez, Rodolfo Miguel (2020)
Small bowel obstruction is the most common surgical disorder in this region of the body. The most common cause is flanges and adhesions, followed by hernias, neoplastic bowel obstruction, and inflammatory bowel disease. The frequency with which obstruction related to these conditions is found varies according to the patient population. The standard treatment has classically been the surgical choice, however, it currently begins with medical or conservative management. Currently available clinical signs, laboratory data, and imaging studies cannot safely differentiate between patients with a simple obstruction and those with a strangulated obstruction before the onset of irreversible ischemia. Leukocytosis, neutrophilia, elevated serum amylase, alkaline phosphatase, lactate dehydrogenase and even procalcitonin have been found as possible markers of severity. These are considered as possible markers of failure of medical management and indicators of surgical management. Problem: Are the elevated levels of leukocyte count, C-reactive protein, procalcitonin, serum amylase and lactate dehydrogenase factors that predict the failure of conservative treatment in patients with intestinal obstruction, treated at the Regional Teaching Hospital of Trujillo, during the period April 2019 - November 2019? Hypothesis: High levels of leukocyte count, C-reactive protein, serum procalcitonin, serum amylase, and lactate dehydrogenase are factors that are associated with the failure of conservative treatment in patients with intestinal obstruction, treated at the Regional Teaching Hospital of Trujillo, during the April period. 2019 - November 2019. Design: case-control study. Population: patients with a diagnosis of intestinal obstruction, treated in the emergency service of the Regional Teaching Hospital of Trujillo, during the period April 2019 - November 2019.